Competence and Morals of an Educator in the Study of Tarbawi Hadith - Supihatul Mahpudoh; Reffin Laily Nur Widyani (SALIHA: Jurnal Pendidikan Islam, 2025)
Educators have a central role in shaping the character and competence of students, so that ideal competency and moral standards are needed in accordance with Islamic values. The tarbawi hadith provides a normative foundation for educators in carrying out their duties professionally and morally. This research aims to examine the competencies and morals that must be possessed by an educator based on the perspective of tarbawi hadith. This study uses a qualitative approach with a literature study method, where data is collected through the analysis of various literature, including relevant books and journals. The results of the study show that an educator must have competencies that include noble morals, compassion, breadth of knowledge, and flexibility in conveying knowledge. In addition, traits such as zuhud, clean soul, sincerity, forgiveness, glory, authority, love for students, understanding of student competence, and consistency in educating are important aspects in shaping the character of an ideal educator. The implications of this study show that educators not only play the role of conveyors of knowledge, but also as moral role models who are able to have a positive influence on students in their academic and social lives